Burnout and technostress during the COVID-19 pandemic: the perception of higher education teachers and researchers - Marrinhas, Daniel José Costa (2022)
The COVID-19 pandemic had significant impacts on the working conditions of teachers and researchers, jeopardizing their mental health and increasing the risk of burnout and technostress. Thus, eHealth literacy may represent an adequate coping mechanism. The purposes of this study were to assess the experiences of burnout and technostress and their relationship with eHealth among higher education teachers and researchers during the pandemic. Using a cross-sectional design and a quantitative approach, 333 participants responded to an assessment protocol which included the Burnout Assessment Tool (BAT), the Computer-Induced Distress scale (CID) and the eHealth Literacy scale (eHEALS). The results verified the prevalence of burnout and technostress, confirmed the existence of significant differences between sociodemographic groups and found correlations between the BAT, the CID and the eHEALS. The findings indicate moderate levels of burnout and technostress, suggest several risk and protective factors to their development, and show a relationship between burnout and technostress. The results highlighted the importance of eHealth during the pandemic as a relevant coping mechanism. Implications of this study are discussed. As there are few studies in this area, there is a need to pay more attention to mental health of teachers and researchers in order to promote their well-being.